Exploring the impact of library instruction on the Human Sciences Research Council staff, in support of achieving their research and academic goals - Pillai, Viveka (Library and Information Studies Centre (LISC), 2021)
This study explored the impact of library instruction (LI) on the Human Sciences Research Council (HSRC) staff, in support of achieving their research and academic goals. The study used a mixed methods sequential explanatory design, which consisted of two separate phases: quantitative data collection followed by qualitative data collection. The researcher surveyed the HSRC staff members, by using two online questionnaires. The first was for staff members who previously attended LI and the second for those who had never attended. A Likert scale was used to gauge the extent to which a participant agreed or disagreed with certain statements posed. A combination of open and closed ended questions were used in the questionnaire. The researcher used the free survey software Google forms to create and disseminate the quantitative questionnaires. The data files were then downloaded from Google forms into an Excel file and uploaded into Statistical Package for the Social Sciences (SPSS) for analysis. Participants volunteered for a follow‐up interview; this option was included in both questionnaires. The researcher had separate semi-structured interview guides for staff who attended and for those who never attended LI. Face‐to‐face and telephonic interviews were used to gather data. Interviewees were asked to sign a consent form, granting the researcher permission to audio record the interview. The total number of staff members, with valid e‐mail addresses that were sampled was 385. The total response rate was 27%. A total of 104 staff responded, with 69 staff members responding to the questionnaire for those who had attended LI and 35 staff responding to the questionnaire for those who had never attended LI. There were 40 staff members who volunteered to be interviewed, the researcher interviewed the first 30 who responded with signed consent forms. The findings illustrated that LI had a positive influence on the ability of the staff to achieve some of their research and academic goals. Participants indicated that they developed and learned new skills by attending LI. They also attributed their ability to find relevant sources, critically evaluate information and use information responsibly iv due to LI. LI however had little influence on staff publishing more, finding and applying for researching funding, or increasing citation counts. The findings provided an opportunity for the HSRC LI team to develop and explore alternative methods to contribute to staff success in these areas. The study also found that the HSRC library could explore the need for alternative instructional models, consider hosting LI sessions for similar post level groupings and consider offering more LI classes so staff could have more opportunities to attend.